Self-care practices and symptom distress experiences of women with preeclampsia - Navarro-Montevirgen, Jeaneth I. (Manila: College of Nursing, University of the Philippines Manila, 2014)
Hypertension in pregnancy remains to be the most common disorder complicating pregnancies worldwide. In the developing world, preeclampsia is one of the maternal mortality. Data and observations in the Philippines setting show the increasing number of cases being documented every year. The presenting clinical picture of women with preeclampsia demonstrates the need for attention and focused nursing care. There is great concern for the prevention of acute presenting symptoms and complications in women with preeclampsia. Better problem identification and subsequent plan of care be established with knowledge on self-care and symptom experiences. Improvement in maternal care, as well as infant care can be ensured. The study serves to fill the gap on knowledge of Filipino women with preeclampsia, self care practices of women on prenatal care, and acute symptoms during the acute phase of preeclampsia. The information generated can benefit health care providers on interventions during the acute care of women with preeclampsia. For nurses, better plan of care can be done, education on prenatal care can be provided. This study derives its conceptual framework on Orem’s Theory on self-care. At any given time an individual has specific self-care abilities as well as therapeutic self-care demands. If there are more demands than abilities, nursing is needed, such as situations during the acute phase of preeclampsia. The objectives of the study are: 1) To determine the symptoms’ distress experiences, patient factors and self-care practices of women with preeclampsia; 2. To determine the association between patient factors, and self-care practices, and symptoms’ distress experiences of women with preeclampsia. -- The study utilized a descriptive correlational design. The following research tools were used to measure the variables: Symptom distress assessment tool and Self-care inventory tool. The participants of the study (n 136) were drawn from two government hospitals that attend to services patients. These hospitals are involved with service, training and research. Inclusion and exclusion criteria were applied. The patients were seen twenty four hours after their delivery. The research is approved by the Ethics Review Board of the NIH-UPM. -- The findings of the study show that Preeclampsia Severe (60%) was the most common diagnosis on admission. The highest reported blood pressure on admission was 220/ 120 mmHg, with one case of 220/ 150 mmHg. Ninety six percent (96%) was classified as Stage 2 hypertension, based on the JNC 7 Classification. Urine albumin on admission was 3 + (52%) and 2+ (43%). Women were on their early term (49%) and pre term (46%) of pregnancy on admission, with 0-2 previous pregnancies. Eighty three percent (83%) of the women were ages 21-40 years old, had high school education (70%), had body mass index (BMI) of above normal (41%) and obese (39%). The following are the reported symptom distress experienced by women with preeclampsia. Agitation, and nausea and vomiting were the most reported distressing experiences. Distress experiences were reported for swelling of the face/ or eyes and hands; weight gain; dull throbbing headache; blurred vision, light sensitivity; abdominal pain usually felt on the right side, underneath the ribs; and pain/discomfort on the right shoulder. Of the patient factors, increased BMI were related to agitation and nausea and vomiting, and age was related to pain on the right shoulder and nausea and vomiting. On the self-care practices, 38% reported having prenatal care, 30% had information on good prenatal diet. They had fair knowledge on eliminating alcohol and avoidance of smoking. Taking the weight as a variable for self care was associated with abdominal pain (usually on the right side), pain on the right shoulder, nausea and vomiting, and decreased urine output. It was found out that the development of self care inabilities was derived from the distress experienced by women with Preeclampsia. The nurse can serve as a key role in assisting women with Preeclampsia in their self care efforts. Implications to support self-care practices of women through prenatal care education can be derived. Recommendation for interventions and nursing standard development during the acute phase of preeclampsia is recommended.
Thesis (Master of Arts in Nursing - Adult Health Nursing) -- University of the Philippines Manila, April 2014.
Bibliography: leaves 62-67.
Keywords: Preeclampsia; Preeclampsia -- Self-care, Health